Penilaian Kinerja Pengelolaan DAS Poleang di Sulawesi Tenggara Berdasarkan Indikator Kondisi Lahan - Hasbullah Syaf; Musram Abadi; Umar Ode Hasani; Al Basri; Laode Kasno Arif; La Gandri (Jurnal Ilmiah Membangun Desa dan Pertanian, 2022)
One of the priority watersheds in Southeast Sulawesi is the Poleang watershed. It is necessary to assess management performance to remain sustainable in its implementation. This research aims to determine the performance of poleang watershed management based on indicators of land conditions and determine recommendations for the direction of sustainable land management policies. The survey methods used in the research and analysis include land criticality, land cover and erosion in calculating carrying capacity. This research resulted in the fact that the land support in the Polean g watershed had a high class with a score of 1.25 based on the critical land sub-criteria. Sub-land cover criteria have an excellent category with a score of 0.5, and the erosion index sub-criterion has a very high category with a score of 1.5. Overall, the carrying capacity of the Poleang watershed is in the moderate category, so it is necessary to maintain land or increase the area of vegetation cover of the Poleang watershed through the application of vegetation conservation methods, technical conservation methods and mechanical conservation methods.